Art of reporting - Puri, Manohar, 1944- (Pragun Publications, 2006)
A reporter should always be the part of the society, which he lives or works in. He should be friendly to the local people. He should have a strong resolve, courage and conviction to report something impartially. A reporter should always have a nose for news; He should always be in pursuance of some unusual news; i.e. ""a dog bites am man"" is not a news, but ""a man bites a dog"" will definitely constitute and interesting news for the peopel. Any one who wants to take upt the reporting profession should have the caliber, capacity and resources to investigate some matter at his personal level.